(untitled) (Journal of Psychiatrists’ Association of Nepal, 2017)
Bir Hospital, the first general hospital with specialist services was established in the country in 1889 A.D. When I came back to Nepal after MBBS in 1971, most of the specialties like Medicine, Surgery, Gynae & Obs, Opthalmology, ENT, Psychiatry, Anesthesiology, Radiology, Emergency department with 24 hours service were there. Paediatric OPD service was available, and children were admitted in Kanti children hospital Kathmandu. So mental health service in Nepal was started in a general hospital with different specialties.